HUBUNGAN KOMPRES HANGAT DENGAN INTENSITAS NYERI PADA IBU NIFAS DENGAN BENDUNGAN ASI DI KLINIK PRATAMA SAM KAMPUNG BARU MEDAN MAIMUN - Desi Yolanda Ginting; Anna Waris Nainggolan; Nova Marianti Purba; Edy marjuang Purba (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Breast milk production can be influenced by two factors, namely production and expenditure. Use a warm compress, namely warm water which is then compressed onto the breasts using a towel. Not infrequently non-medical therapy as above is often applied to postpartum mothers whose breast milk has not yet come in, of course first by conducting training with the puskesmas coordinator midwife, to improve maximum service. The research was carried out by determining the initial level of pain intensity (pretest) before giving a warm compress and then continuing with measuring the pain intensity (posttest) after giving a warm compress. The results of the Independent sample t test showed P Value = 0.001, meaning p < 0.05, stating that there is a relationship between warm compresses and pain intensity in mothers with breast milk dams at the Pratama SAM Kampung Baru Clinic, Medan Maimun in 2023. Other research on the effectiveness of compresses Varney said that warm compresses are considered the right action to relieve pain, and for some women who experience problems with breast milk, it is known that using warm compresses alternately can provide a feeling of comfort. Apart from that, the intense pain when there is a blockage in the breast means that mothers tend to choose the easiest method, one of which is a warm compress.